PFOh No: Spontaneous Globe Rupture During Injection of Perfluoro-n-Octane (PFO) During Retinal Detachment Repair - Hammer, Jon David; Khurshid, Syed Gibran (Frontiers in Medicine, 2020)
The authors describe a case of spontaneous globe rupture during instillation of perfluoro-n-octane (PFO) during retinal surgery. A 71-year-old male with a macular-involving rhegmatogenous retinal detachment underwent pars plana vitrectomy. During instillation of PFO manually on a single bore cannula by the assisting resident spontaneous globe rupture occurred superotemporally in an area with no visible underlying structural abnormalities. Factors that led to this complication include use of single bore cannula, error in judgment of resistance during PFO injection, and inexperience. This is the first report of this complication without an identifiable structural abnormality predisposing patient to perforation.